Speaking to the outraged: discursive responses of policy elites to social unrest over economic issues. Issue 4 (2nd October 2019) - Avigur-Eshel, Amit
ABSTRACT: Communicative discourse is widely understood as consisting of a top-down political dynamic in which policy elites actively construct discourse and convey it to a passive public. Yet, this understanding overlooks instances of a bottom-up dynamic where social unrest puts policy elites in a reactive position. Relying on the literature on depoliticization, I argue that in bottom-up dynamics, policy elites use a different discursive tactic than in top-down dynamics, namely, containment. Using the containment tactic, policy elites accommodate their discourse to engage with public pleas in a manner that reaffirms the ideational framework that currently underlies policymaking, by using two complementary practices: boundary-setting and tailored framing. I illustrate my argument through an analysis of the Israeli policy elite's public discursive responses to a period of mass protest during 2011. The article concludes by pointing out the rising importance of studying communicative discourse in bottom-up political dynamics.